Determining the causes of structural fire due to electrical fault in dwelling - Ahmad Faiz, Tharima @ Zainuddin (2011)
Among natural disasters, fires seem to be impossible to deal with, as they bring misery to human life, incur losses of property as well as giving the worst impact to the national economic stability. Electrical home fire is commonly caused by either wiring system or electrical appliances. This study was carried out to assess the level of practice on electrical appliances and wiring system among fire victims as well as to study the factors related to overload. A total of 77 respondents from 3 states (Negeri Sembilan, Pahang and Terengganu) were involved in this study. The respondents were chosen through universal sampling. A survey through telephone calls among fire victims in the dwelling houses was conducted to obtain information on their practice which could lead to electrical fault. Results showed that the most common type of dwelling involved in residential fire was typical kampong houses (35.1%). In addition, the most commonly used electrical appliances by the fire victims were television (93.5%), fluorescent lamp (90.9%), washing machine (88.4%), rice cooker (88.3%), iron (77.9%) and ceiling fan (74%). Descriptive analysis showed that 54.5% of fire victims obtained less than 59.4 of mean scores, indicating that they had poor practices toward electrical appliances failure. In comparison, the T-Test revealed that there was a significant difference in practice scores between those who performed good practices and poor practices on electrical appliances failure (p<0.001). Most of the respondents (>50%) performed poor practice in all domains (poor connection, short circuit, aging and lightning) except for overload. Multiple linear regression analysis showed that there was a significant relationship between overload and factors such as poor connection (β = 0.318; p = 0.002), aging (β = 0.300; p = 0.003), appliances failure (β = 0.233; p = 0.022) and portable cooking (β = 0.277; p = 0.015). In conclusion, the level of practice on wiring system among fire victims towards warning signs of danger and experience is considered below the satisfactory level. According to the coefficient values order, wiring systems (poor connection, aging, appliances failure) and electrical appliances (portable cooking) were the common causes to overload before leading to electrical fire in dwelling.